Effect of fat replacement by fructooligosaccharide in hamburger: physicochemical, technological and sensorial analysis - Hartmann, Giovanna; Teixeira, Flávia; Soares, Jaqueline Machado; Silva, Kátia Aparecida da; Schwarz, Kélin; Schiessel, Dalton Luiz; Novello, Daiana (International Journal for Innovation Education and Research, 2020)
The aim of this study was to evaluate the influence of fat substitution by fructooligosaccharide on physicochemical, technological and sensory characteristics of hamburgers. Five hamburgers formulations were prepared: F1 - standard (0% FOS) and the others added 1.25% (F2), 2.50% (F3), 3.75% (F4) and 5% (F5) of FOS. The Acceptability similar to standard sample was found for hamburgers with up to 3.75% prebiotic addition. However, all formulations had acceptability index above 70%. Cooking yield, moisture retention, shrinkage and fat retention have been increased as FOS was added. Substitution of fat by FOS increased carbohydrate and fiber content and decreased lipid and calorie hamburgers content. FOS addition did not change red and yellow values, however it increased brightness of product. FOS is an ingredient with potential for addition in beef hamburger, improving physicochemical and technological parameters and with little influence on sensory characteristics.